Можливості штучного інтелекту для захисту прав людини - Щолкін, М. М. (ХНУРЕ, 2023)
Artificial intelligence is a promising technology that can help solve various problems in different fields. The use of AI in the field of human rights can help ensure more efficient and transparent management of human rights and significantly improve their protection. However, it is necessary to take into account possible challenges, such as the lack of data reliability and privacy protection, as well as ethical and legal aspects of using AI in this area. To ensure the success of AI in human rights, it is necessary to continue research and development of new technologies, as well as to ensure the responsible use of these technologies, considering ethical and legal aspects.